2010
DOI: 10.1111/j.1432-2277.2009.00973.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of regulatory T Cells and selection of highly potent CD62L+ cells during treatment of human lung transplant recipients with rapamycin

Abstract: Summary The currently available immunosuppressive agents applied in human transplantation medicine are highly potent in the protection from acute allograft rejection. However, long‐term allograft survival is still poor as these drugs fail to sufficiently prevent chronic allograft rejection. Naturally occurring regulatory T cells have been postulated as the key players to establish long‐lasting transplantation tolerance. Thus, the development of immunosuppressive regimens which shift the pathological balance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
(43 reference statements)
3
11
1
Order By: Relevance
“…This down-regulation of immunity to vector-mediated dystrophin expression may be mediated by Treg cells, as the ratios of Treg cells to both CD4 + and CD8 + effector T cell populations increased in RAPA-treated, vector-injected TA muscles compared to the mice that received either only the vector, or blank beads and vector. The effect of RAPA on selective survival of Treg cells, which can then lead to the increase of their ratio over effector CD4 and CD8 T cells shown in our study, is in agreement with previous findings where RAPA induced preferential expansion of Treg cells in other studied tissues21223132. Furthermore, this study demonstrates RAPA bead-mediated suppression of humoral immunity specific to recombinant murine dystrophin expression, although variability between mice and small sample size limit the strength of conclusions that can be drawn from this observation.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This down-regulation of immunity to vector-mediated dystrophin expression may be mediated by Treg cells, as the ratios of Treg cells to both CD4 + and CD8 + effector T cell populations increased in RAPA-treated, vector-injected TA muscles compared to the mice that received either only the vector, or blank beads and vector. The effect of RAPA on selective survival of Treg cells, which can then lead to the increase of their ratio over effector CD4 and CD8 T cells shown in our study, is in agreement with previous findings where RAPA induced preferential expansion of Treg cells in other studied tissues21223132. Furthermore, this study demonstrates RAPA bead-mediated suppression of humoral immunity specific to recombinant murine dystrophin expression, although variability between mice and small sample size limit the strength of conclusions that can be drawn from this observation.…”
Section: Discussionsupporting
confidence: 94%
“…The immunosuppressive drug, RAPA, has demonstrated suppression of immunity in multiple clinical applications2021. Mechanisms of action of RAPA for immune suppression include Treg expansion, inhibition of effector T cell activation and proliferation, and prevention of inflammatory cytokine production222324.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, RAPA has been used widely in various studies to expand or select for Foxp3 + Tregs (15,16,(31)(32)(33). In contrast to the inhibitory effect of RAPA on proliferation of effector T cells, Tregs proliferate and function in the presence of RAPA (15,16,26,33 We demonstrated that RAPA administration ameliorated the dystrophic phenotype of mdx muscle. There was a significant reduction of muscle fiber necrosis in both TA and Dia muscles of the mdx mouse.…”
Section: Discussionmentioning
confidence: 77%
“…The activation of mTOR by phosphorylation in the presence of energy, nutrients or growth factors is known to be important for muscle fiber growth (26), and RAPA can block this activation. Therefore, we examined the level of mTOR activation in TA and Dia muscles of 6-wk-old (during active necrosis) and 12-wk-old (after the peak of active necrosis) age-matched untreated mdx and wild-type B10 mice.…”
Section: Mtor Activation Differs Between Ta and Dia Muscles Of MDX Mousementioning
confidence: 99%
“…Rapa is routinely used in the clinics to prevent allograft rejection(51), and is currently being tested as a therapy for autoimmunity(52, 53). In most reports, the clinical formulation of rapa (Sirolimus) boosts both number and function of Tregs (53-55).…”
Section: Discussionmentioning
confidence: 99%